Modulation of the Surface Proteome through Multiple Ubiquitylation Pathways in African Trypanosomes. - Martin Zoltner; Ka Fai Leung; Sam Alsford; David Horn; Mark C Field (PLoS Pathogens)
Recently we identified multiple suramin-sensitivity genes with a genome wide screen in Trypanosoma brucei that includes the invariant surface glycoprotein ISG75, the adaptin-1 (AP-1) complex and two deubiquitylating enzymes (DUBs) orthologous to ScUbp15/HsHAUSP1 and pVHL-interacting DUB1 (type I), designated TbUsp7 and TbVdu1, respectively. Here we have examined the roles of these genes in trafficking of ISG75, which appears key to suramin uptake. We found that, while AP-1 does not influence ISG75 abundance, knockdown of TbUsp7 or TbVdu1 leads to reduced ISG75 abundance. Silencing TbVdu1 also reduced ISG65 abundance. TbVdu1 is a component of an evolutionarily conserved ubiquitylation switch and responsible for rapid receptor modulation, suggesting similar regulation of ISGs in T. brucei. Unexpectedly, TbUsp7 knockdown also blocked endocytosis. To integrate these observations we analysed the impact of TbUsp7 and TbVdu1 knockdown on the global proteome using SILAC. For TbVdu1, ISG65 and ISG75 are the only significantly modulated proteins, but for TbUsp7 a cohort of integral membrane proteins, including the acid phosphatase MBAP1, that is required for endocytosis, and additional ISG-related proteins are down-regulated. Furthermore, we find increased expression of the ESAG6/7 transferrin receptor and ESAG5, likely resulting from decreased endocytic activity. Therefore, multiple ubiquitylation pathways, with a complex interplay with trafficking pathways, control surface proteome expression in trypanosomes.